Increasing Understanding Regarding Free Legal Aid in the Implementation of Women's Rights Protection - Kurnianingsih, Marisa; Aprilia, Lina; Dita Nadya Anastasya; Kuswardani, Kuswardani; Surbakti, Natangsa (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This community service is carried out to increase understanding regarding legal aid, which is one of the efforts to protect women's rights legally. Equality between women is the foundation of ensuring legal protection for women because it includes efforts to provide access to justice for all individuals. As a rule of law, Indonesia guarantees the safety of women's rights, including the right to access legal aid. This community service is carried out using the socialization method. Socialization is carried out by holding discussions covering issues such as gender crimes, the protection of women from violence and exploitation, as well as the need for effective responses to violations of women's human rights. The